Stability analysis of Al2O3/water nanofluids. Issue 1 (1st January 2017) - Choudhary, Rajesh; Khurana, Deepak; Kumar, Aditya; Subudhi, Sudhakar
ABSTRACT: This paper presents the stability analysis of Al2 O3 /water nanofluid. The stability is investigated with the help of zeta potential and visual inspection methods. The effects of pH and sonication time for the stability of nanofluids are studied in detail. The visual inspection method is used to calculate the stability period of nanofluids. The zeta potential is directly related to stability period of nanofluids; higher the absolute value of zeta potential, higher the stability period. The stability is also analysed by using sodium dodecyl sulphate, a surfactant, with respect to the time elapsed after the preparation of nanofluids.